Safety of palliative cancer patients using morphine for pain control: scoping review - Janillê Luciana Araújo; Erica Brandão de Moraes; Barbara Pompeu Chistovam; Aline Lima Pestana Magalhães (BrJP)
BACKGROUND AND OBJECTIVES: The objective of this study was to map the safety practices of morphine use for pain control in palliative cancer patients. CONTENTS: This is a scoping review that followed the methodology of the Joanna Briggs Institute (JBI) to answer the question: what is the evidence on safety practices for the use of morphine for pain control in palliative cancer patients? The search was carried out in the Medline, LILACS, Scopus, Embase, Web of Science, Cochrane and CINAHL databases, as well as in the gray literature. The titles and abstracts were evaluated by two independent reviewers, and the selected papers were read in full. The data extracted is presented in the form of tables accompanied by a narrative summary. The 21 articles selected identified 14 service management practices in the use of morphine, 24 safety practices related to the prescription of morphine, 15 safety practices related to the preparation and administration of morphine and characterized 16 risks and 8 adverse reactions. CONCLUSION: Through the identified practices, professionals can plan safe care, managing risks, adverse reactions, and promoting better control of cancer pain. Keywords: Adverse effects, Drug-related adverse reactions, Morphine, Pain management, Patient safety.